Advancing Christian unity - Burgess, Anthony, -1664; Vogan, Matthew (Grand Rapids Reformation Heritage Books, 2019)
"An exposition of the topic of Christian unity in John 17"--
Includes bibliographical references.
Keywords: Bible. -- Sermons -- Early works to 1800.; Church -- Unity -- Sermons -- Early works to 1800.; Sermons, English -- 17th century